Pengaruh Inflasi, Tingkat Suku Bunga, Nilai Tukar, dan Struktur Modal terhadap Return Saham Perusahaan Sektor Farmasi - Mourine, Angelina; Septina, Fanny (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
Return is one of the factors that can motivate investors to invest. There are two factors that can affect the rate of return, there are macro and microeconomic factors This study aims to determine the effect of macroeconomic factors, such as inflation, interest rates, and exchange rates and microeconomic factors, there are capital structure on stock returns in pharmaceutical sector companies listed in Indonesia Stock Exchange for the 2015-2020 period. This research is a quantitative approach, there are calculations on the data in the form of numbers. The research sample uses pharmaceutical companies that have been listed on the IDX for the 2015-2020 period using a purposive sampling technique, obtained 48 samples of the company during the 2015-2020 period. The research is secondary data which is already available about financial reports and annual reports of pharmaceutical sector companies for the 2015-2020 period and obtained from Indonesian Stock Exchange official website. The results showed that inflation have a significant effect on stock returns, interest rates have a significant effect on stock returns, the exchange rate have no significant effect on stock returns, capital structure have no significant effect on stock returns, and company size as a control variable do not have a significant effect on stock returns in pharmaceutical companies listed on the IDX for the 2015-2020 period.Keywords : Exchange Rates, Capital Structure, Inflation, Interest Rates, Stock Returns